2021
DOI: 10.1093/ndt/gfab277
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity in kidney transplantation: a prospective cohort study from French registries between 2008 and 2014

Abstract: Background The access of obese patients to kidney transplantation is limited despite several studies showing that obese transplant recipients had a better survival rate than those undergoing dialysis. The aim of this study was to compare patient and graft survival rates and post-renal transplant complications in obese patients and non-obese patients and to assess the effect of pre-transplant weight loss in obese patients on transplant outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It is noteworthy that a higher graft survival was also found in patients with obesity who lost more than 10% weight compared to patients with obesity and without weight loss. However, that research did not find a relationship between obesity or weight loss with mortality after transplantation [39].…”
Section: Outcomes and Complications Of Transplant Surgery Impact Of O...mentioning
confidence: 86%
“…It is noteworthy that a higher graft survival was also found in patients with obesity who lost more than 10% weight compared to patients with obesity and without weight loss. However, that research did not find a relationship between obesity or weight loss with mortality after transplantation [39].…”
Section: Outcomes and Complications Of Transplant Surgery Impact Of O...mentioning
confidence: 86%
“…The patient survival in patients with a high BMI was associated with significantly increased mortality in both subgroups of graft sources (LD, p = 0.045; DD p = 0.004). However, in a prospective cohort study from French registries they presented a lower graft survival but similar patient survival in patients with grade 1 obesity [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity among KTx recipients and its association with graft outcomes was another area of study. Obesity was associated with decreased graft survival, more DGF, increased postoperative surgical complications, [24][25][26] longer procedure duration, and longer warm ischemia time. 27 Tsapepas et al found that body mass index (BMI) ≥35 was associated with increased surgical site infections on multivariable analysis (adjusted OR 3.34; 95% CI 1.55-7.22; P = .022), though this study did not find the increased rate of graft failure in obese patients that was found in prior studies.…”
Section: Obesitymentioning
confidence: 95%
“…However, there was a confounding variable, as the weight loss group also had an increased duration of dialysis compared to the group that did not lose weight. 24 Finally, Jarrar et al found through a retrospective cohort study of over 200 000 transplants that donor obesity in combination with recipient obesity further increases the risk for graft loss and DGF over recipient obesity alone. 29 These findings all point to an increased risk of negative outcomes seen in renal transplantation in the setting of obesity.…”
Section: Kidney Transplantationmentioning
confidence: 99%